Use of the Remaining Sample from the Panbio COVID-19 Antigen Rapid Test Device for the Molecular Screening of the SARS-CoV-2 Variant of Concern B.1.1.7 - Montes, Milagrosa; M. Marimón, José; D. Piñeiro, Luis; Martin-Peñaranda, Tania; Gomez-Ruiz de Arbulo, Marta; Cilla, Gustavo (International Journal of Clinical Microbiology, 2021)
Objective Real-time surveillance of SARS-CoV-2 variants of concern (VOC) is of essential public health importance. Rapid Antigen Detection Tests (RAgDT) have become first-line COVID-19 diagnostic methods in many regions, but this strategy can hamper the surveillance of the virus variants due to their decentralized performance. The aim of this study was to assess the usefulness of the remaining sample of a widely used RAgDT (Panbio) for the surveillance of the B.1.1.7 VOC using molecular methods. Methods Symptomatic individuals and asymptomatic close contacts of confirmed cases were routinely screened for SARS-CoV-2 infection using the RAgDT in Primary Health Care Centers. After performing the test, the extraction tubes containing the remaining biological material of RAgDT-positive cases were sent to the clinical microbiology laboratory where RT-PCRs detecting key mutations of the VOC were conducted. Results A valid result was obtained in 1770/1812 (97.7%) RAgDT-positive cases. Variant B.1.1.7 was detected in 34.7% of the patients, increasing from 0% to 87.7% between the weeks beginning January 4 and March 15, 2021. Conclusion The sample remaining after performing the Panbio RAgDT allowed to monitor the emergence and circulation of the B.1.1.7, greatly improving the population screened for the molecular study of SARS-CoV-2 variants.
Keywords: COVID-19; SARS-CoV-2; antigen testing; B.1.1.7 variants; RT-PCR testing